PENGARUH TERAPI REFLEKSI KAKI TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI KECAMATAN CAMPURDARAT KABUPATEN TULUNGAGUNG - Angga Miftakhul Nizar; Farida Farida (Jurnal Penelitian, 2022)
Hypertension is a contributor to death from non-communicable diseases by 60%. The purpose of this study was to determine the effect of giving foot reflexology therapy on blood pressure in the elderly in Campurdarat District. The research design used a quasi-experimental approach with a pre-post test design approach. The number of research samples was 116 respondents who were selected using purposive sampling. The results showed that the difference in mean blood pressure before and after foot reflexology therapy was 14 mmHg for systolic and 11 mmHg for diastolic. Based on the statistical paired T Test where the level of significance or p (0.05) obtained a P value of 0.001 so that the P value value, therefore there is the Effect of Foot Reflexology Therapy on Blood Pressure in Hypertensive Elderly in Campurdarat District, Tulungagung Regency in 2022. The results of This study proves that reflection therapy can reduce blood pressure in the elderly with hypertension. The provision of foot reflexology therapy must be balanced with regular exercise, control of diet, and consumption of drugs according to indications to get optimal results.